Implementation of Inclusive Education for Children With Special Needs in Indonesia - Hikmat Hikmat (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Inclusive education is a sort of equity and nondiscriminatory education in which children with and without disabilities receive the same education. Inclusive education is a type of special education that requires all children with disabilities to get an education on a par with their peers. Until now, children with varying abilities (disabled) have received unique educational facilities called Special Schools that are adapted to their degree and kind of disability (SLB). Inadvertently, the special education system has erected a barrier of exclusivity for students with disabilities. Implementing inclusive education for children with special needs should generate a pleasant, welcoming environment and build students' confidence in their ability to get an appropriate education according with their rights. In Indonesia, inclusive schools are still not being implemented according to the concepts and rules proposed, both in terms of pupils, teacher credentials, facilities and infrastructure, and parental and community support. Inclusion in education is still a relatively new phenomena in Indonesia.